2016
DOI: 10.5433/1679-0359.2016v37n3p1617
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation of beef and buffalo extensively reared and its relationship to sociodemographic characteristics of consumers

Abstract: Sensory characteristics of meat from different animal types, including cattle (Angus and Brangus) and buffalo raised at pasture, and information on socio-demographic determinants of consumer preference were evaluated. Samples of roasted rib eye were cut and served in a disordered and monadic manner to 188 untrained tasters. A nine-point hedonic scale was used to assess odor, color, tenderness, succulence and overall appearance. Analysis of variance was carried out using the GLM procedure of SAS®, considering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For most of the traits, the minimum values are quite low, indicating poor perceived quality, but on the other hand, the highest scores in the range are often close to the best extreme of the scale, thus proving that buffalo meat can reach a satisfactory organoleptic quality, similar if not superior to that of beef. For example, buffalo meat evaluated by a consumer panel obtained a higher score for tenderness compared to that of Angus breed reared in the same conditions [146]. When compared to the Simmental breed, buffalo meat was rated by consumers as better in flavour, and this resulted in a higher overall liking, but only when cooked [17].…”
Section: Trait (Scale) Rangementioning
confidence: 98%
See 1 more Smart Citation
“…For most of the traits, the minimum values are quite low, indicating poor perceived quality, but on the other hand, the highest scores in the range are often close to the best extreme of the scale, thus proving that buffalo meat can reach a satisfactory organoleptic quality, similar if not superior to that of beef. For example, buffalo meat evaluated by a consumer panel obtained a higher score for tenderness compared to that of Angus breed reared in the same conditions [146]. When compared to the Simmental breed, buffalo meat was rated by consumers as better in flavour, and this resulted in a higher overall liking, but only when cooked [17].…”
Section: Trait (Scale) Rangementioning
confidence: 98%
“…In fact, the consumers' evaluation can be affected not only by variables that can be easily taken into account, such as sex and age, but also by psychological emotions, which are much more difficult to analyse [145]. An investigation into the relationships between the sociodemographic profile of the consumers and the sensory evaluation of buffalo meat and beef [146] revealed that the gender of the assessors did not influence any of the sensory traits, whereas the age affected odour and colour, with people over 50 giving higher scores. However, the main determinant for four out of the five sensory traits was income, with low-income people giving the highest scores.…”
Section: Trait (Scale) Rangementioning
confidence: 99%
“…Andrighetto-Canozzi et al [100] analyzed the sensory properties of meat from castrated Murrah buffaloes with an initial average age of 15 months, slaughtered at 75, 100, 125, or 150 days of the feedlot. The authors concluded that the confinement time did not influence the physicochemical and sensory characteristics of the meat of young Murrah buffaloes.…”
Section: Sensory Propertiesmentioning
confidence: 99%
“…The reduction in the genetic variability of these populations, in addition to the common origin, is a further point of convergence between the purebred individuals from tropical herds of bovine and buffalo species in Brazil (Marcondes et al, 2014). Since the last importation of animals from India in 1962, both in Brazil and India, breeding animal selection programs have been developed, aiming at genetic improvement to increase milk productivity (Marques et al, 2019), as well as meat quality (Cassiano et al, 2004;Canozzi et al, 2016).…”
Section: Cattle and Buffalo Herd Formation In Brazil And Its Impact Omentioning
confidence: 99%